Psychiatry, bio-epistemes and the making of adolescence in southern Brazil - Dominique Pareja Béhague (História, Ciências, Saúde: Manguinhos)
Abstract Drawing on an ethnographic study in southern Brazil, this paper explores how therapists’ attempts to “resist bioreductionist” pharmaceutical use both succeed and crumble. Using a comparative framing, I show that pharmaceuticalization can become an anesthetizing “lid” that interacts with young people’s polarizing micro-politics and is an outgrowth of multi-generational medico-political family histories. This lid, however, is not air-tight and exceptionalities are born out of these very same histories. I argue that both pharmaceuticalization and exceptions to it emerge not through “resistance” to biopsychiatric logics but from the transformative possibilities that the patterned co-production of social, political, and psychiatric life affords.